Thiamine responsive megaloblastic anaemia complicated with acute Parvovirus infection: a case report - Khaliq, Sehar (Journal of the Pakistan Medical Association, 2022)
Thiamine responsive megaloblastic anaemia syndrome also known as Rogers syndrome is a very rare autosomal recessive disorder. The hallmark of the disease is the presence of the classic triad of anaemia, diabetes mellitus, and sensorineural deafness. We report the case of a 14-year-old boy who presented to us with severe megaloblastic anaemia, diabetes mellitus, and sensorineural deafness. The anaemia was further complicated by acute parvovirus infection. He was put on high doses of thiamine (vitamin B1) which led to an improvement. Key words: Thiamine, Megaloblastic Anaemia, Deafness, Diabetes Mellitus.